Identifikasi Perubahan Penggunaan Lahan Agroforestri di Pulau Pahawang - Fatimah Azzahra Nurul Afifah; Indra Gumay Febryano; Trio Santoso; Arief Darmawan (Journal of Tropical Marine Science, 2021)
Agroforestry plays an important role in supporting ecological, economic, and social aspects of small islands. This study aims to determine the dynamics of agroforestry land use in Pahawang Island. The method used the digital image interpretation technique with Geographical Information System (GIS) analysis on agroforestry land-use dynamics in 2006, 2014, and 2019. The research procedure is to classify images of forests, agroforestry, mangroves, fish pond, and settlements. Then, the land classification data being verified by ground checks to determine the accuracy of the data. Validity test used a confusion matrix, and a depth interview was conducted to determine the phenomena in the 2006–2014 period—the results obtained with an image accuracy rate in 2019 of 92.53%. The results show that there is an increasing and decreasing in the agroforestry land. The decreasing is due to the practice of buying and selling land by tourism investor. Partnership schemes and community-based tourism development can be carried out while maintaining the existing agroforestry conditions to support the sustainability of Pahawang Island.